Ultrasound Morphometry and Mean Echogenicity of Digital Flexor Tendons, Suspensory Ligament, and Accessory Ligament of Digital Deep Flexor Tendon in Gaited Horses - Schade J.* (2023)
© 2023 by the authors.The objective of this study was to evaluate and compare the sonographic characteristics of the digital flexor tendons and ligaments of the palmar/plantar of the metacarpal and metatarsal regions in gaited horses, as well as to establish normal reference ultrasound values for Mangalarga Marchador (MM) and Campeiro breeds. Transverse sonographic images were obtained of 50 adult and healthy horses from the MM (n = 25) and Campeiro (n = 25) breeds. The images were taken in six metacarpal/metatarsal zones, and the following measurements were taken: transverse area, circumference, dorsopalmar/plantar length, lateromedial length, and mean echogenicity. Differences were observed between breeds in the fore- and hindlimbs, and, even when not significant, the Campeiro breed tended to have higher values for most variables and structures. Variations between zones and between structures in the same zone followed a similar trend in both breeds for all variables. In addition, the dimensions and variations between zones and structures were different between the fore- and hindlimbs, highlighting the need for specific values for the digital flexor tendons and ligaments of the metatarsal plantar region. In conclusion, the digital flexor tendons, suspensory ligaments, and accessory ligaments of the digital deep flexor tendon are influenced by the breed factor in gaited horses, and they are different between the fore- and hindlimbs.